Augmentative and Alternative Communication Strategies for Learners with Diverse Educational Needs in African Schools: A Qualitative Literature Review - Ariné Kuyler; Gloria R. Ledwaba; Mary G. Clasquin-Johnson; Jacomina M. C. Motitswe; Emile Gouws; Tshifhiwa I. Mashau; Margaret Chauke; Ensa Johnson (Disabilities)
Augmentative and Alternative Communication (AAC) research highlights the critical role of collaborative efforts among communication partners in supporting children with diverse educational needs in the school setting. This study aims to describe AAC strategies and systems employed in African schools to facilitate participation for learners with diverse educational needs. A qualitative literature review was employed to describe 18 studies involving 659 participants across special schools and inclusive classrooms. The participants included 488 learners with diverse educational needs and 171 teachers. The research designs predominantly featured quantitative approaches, with some mixed-methods studies. This study found that reviewing classroom instruction strategies, learning processes, participant proficiency, and AAC strategies is cardinal for communication participation within the classroom. However, outcomes varied widely due to factors including learner characteristics and contextual familiarity. Key outcomes included improved use of the AAC system labeling and the identification of different symbols. Recommendations for further research include increased professional training and the development of collaborative AAC services. The findings underscore the need for a collaborative approach to AAC implementation, further research, and enhanced training to address the diverse needs of learners and promote the sustainability of AAC use.